Identification of new aryl hydrocarbon receptor (AhR) antagonists using a zebrafish model. Issue 19 (1st October 2019) - Jeong, Jieun; Kim, Kun-Hee; Kim, Dong-Young; Chandrasekaran, Gopalakrishnan; Kim, Minhee; Pagire, Suvarna H.; Dighe, Mahesh; Choi, Eun Young; Bak, Su-Min; Kim, Eun-Young; Shin, Myung-Geun; Choi, Seok-Yong; et al.
Graphical abstract: Abstract: A new series of 1, 3-diketone, heterocyclic and α, β-unsaturated derivatives were synthesized and evaluated for their AhR antagonist activity using zebrafish and mammalian cells. Compounds 1b, 2c, 3b and 5b showed significant AhR antagonist activity in a transgenic zebrafish model. Among them, compound 3b, and 5b were found to have excellent AhR antagonist activity with IC50 of 3.36 nM and 8.3 nM in a luciferase reporter gene assay. In stem cell proliferation assay, compound 5b elicited marked HSC expansion.